Systemic doxycycline as an adjunct to scaling and root planing in diabetic patients with periodontitis: a systematic review and meta-analysis - Kenneth Chou Hung Yap; Shaju Jacob Pulikkotil (BMC, 2019)
Abstract Background To compare the effectiveness of systemic doxycycline as an adjunct to scaling and root planing (SRP) with SRP alone in improving periodontal clinical attachment level and glycemic control in diabetic patients with periodontitis. Methods Two independent reviewers (KY and SJ) screened two electronic databases, PubMed and Scopus, for randomized clinical trials on the use of systemic doxycycline as an adjunct to scaling and root planing in improving periodontal status and glycemic control in diabetic patients with periodontitis using predetermined selection criteria within a 3-month period. The reviewers independently did data screening, data selection, data extraction and risk of bias. Quality of studies involved was analysed using the revised Cochrane Risk of Bias 2.0. Weighted standard mean differences (SMD) and 95% confidence intervals were calculated using a random effects meta-analysis model. Publication bias was evaluated using funnel plot. Quality of evidence was evaluated by Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results Electronic searches provided 1358 records and six studies were selected. The meta-analyses indicated that there was no statistically significant difference in the improvement of periodontal status with the use of systemic doxycycline as an adjunct for scaling and root planing (SRP). SMD of clinical attachment levels (− 0.22 [− 0.52, 0.08]) and HbA1c levels (− 0.13 [− 0.41, 0.15]) were calculated. Overall risk of bias is high in 2 out of 6 studies involved. Conclusion Systemic doxycycline when used in addition to scaling and root planing yields no significant improvement of clinical attachment levels for periodontal status and reduction of HbA1c levels in treatment of diabetic patients with periodontitis when comparing the test group to the control group.